2012
DOI: 10.3391/mbi.2012.3.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colonial tunicate presence on Ciona intestinalis recruitment within a mussel farming environment

Abstract: The colonial tunicate Clavelina lepadiformis is a recent invader to the northwest Atlantic and has the potential to cause ecological and economic harm. This paper provides a review of the biological and ecological characteristics of C. lepadiformis, and hypothesizes the likely mechanisms of introduction, establishment and future expansion. The intent of this paper is to provide a consolidated source of information for marine ecosystem managers and provide a starting point for developing a management strategy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…lasted longer at site B than at site A. In contrast to previous studies that reported negative effects of colonial ascidians on other colonizers [11,14], we found that the presence of this compound ascidian had a positive or no influence on the presence of the highly abundant fouler Obelia sp. as well as on the total cover by fouling organisms that established on the settlement tiles in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…lasted longer at site B than at site A. In contrast to previous studies that reported negative effects of colonial ascidians on other colonizers [11,14], we found that the presence of this compound ascidian had a positive or no influence on the presence of the highly abundant fouler Obelia sp. as well as on the total cover by fouling organisms that established on the settlement tiles in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Helgoland Marine Research *Correspondence: mlenz@geomar.de 2 Marine Ecology Department, GEOMAR Helmholtz Centre of Ocean Research Kiel, Duesternbrooker Weg 20, 24105 Kiel, Germany Full list of author information is available at the end of the article influence the settlement and recruitment of other organisms or the succession of communities [11][12][13][14].…”
Section: Open Accessmentioning
confidence: 99%
“…As sloughing creates bare space on the longline, it would be relatively straightforward to assess the magnitude of this effect during routine monitoring. Crop sloughing resulting from the weight of excess biofouling has been described in other musselgrowing localities that experience significant oversettlement of the culture species by biofoulers; most notably in eastern Canada, where excessive biofouling by tunicates (especially Ciona intestinalis) has been an ongoing problem for >10 yr (Carver et al 2003, Ramsay et al 2008, Paetzold et al 2012. In Prince Edward Island, one of the measures employed to reduced crop loss by sloughing is to 'double sock' individual dropper lines (Bakker et al 2011).…”
Section: Perna Crop Yield and Impact Of Mytilusmentioning
confidence: 99%
“…For instance, the absence of S. clava and Ciona spp. is of particular interest, as these solitary ascidians are present at adjacent inshore locations and have been associated with operational interference or crop loss at inshore sites in New Zealand (Forrest et al ) and globally (Carver et al ; Ramsay et al ; Paetzold et al ). Other recognized nuisance species were also absent from Opotiki, including the colonial ascidian D. vexillum ; the Asian kelp, U. pinnatifida ; and the blue mussel, M. galloprovincialis .…”
Section: Discussionmentioning
confidence: 99%